Critical success factors for routine immunization performance: A case study of Zambia 2000 to 2018. (August 2022) - Micek, Katie; Hester, Kyra A.; Chanda, Chama; Darwar, Roopa; Dounebaine, Bonheur; Ellis, Anna S.; Keskinocak, Pinar; Leslie, Abimbola; Manyando, Mwangala; Sililo Manyando, Maurice; Nazzal, Dima; Awino Ogutu, Emily; et al.
Highlights: This paper describes how policies and programs contributed to improved vaccine coverage in Zambia. Communication, coordination, and collaboration between implementing levels were imperative. Adjacent successes in health systems strengthening and governance were leveraged. Policies in Zambia include flexibility in implementation for tailored approaches in each district. Abstract: Introduction: The essential components of a vaccine delivery system are well-documented, but robust evidence on how and why the related processes and implementation strategies prove effective at driving coverage is not well-established. To address this gap, we identified critical success factors associated with advancing key policies and programs that may have led to the substantial changes in routine childhood immunization coverage in Zambia between 2000 and 2018. Methods: We identified Zambia as an exemplar in the delivery of childhood vaccines through analysis of DTP1 and DTP3 coverage data. Through interviews and focus group discussions at the national and subnational levels, we investigated factors that contributed to high and sustained vaccination coverage. We conducted a thematic analysis through application of implementation science frameworks to determine critical success factors. We triangulated these findings with quantitative analyses using publicly available data. Results: The following success factors emerged: 1) the Inter-agency Coordinating Committee was strengthened for long-term engagement which, complemented by the Zambia Immunization Technical Advisory Group, is valued by the government and integrated into national-level decision-making; 2) the Ministry of Health improved the coordination of data collection and review for informed decision-making across all levels; 3) Regional multi-actor committees identified development priorities, strategies, and funding, and iteratively adjusted policies to account for facilitators, barriers, and lessons learned; 4) Vaccine messaging was disseminated through multiple channels, including the media and community leaders, increasing trust in the government by community members; 5) The Zambia Ministry of Health and Churches Health Association of Zambia formalized a long-term organizational relationship to leverage the strengths of faith-based organizations; and 6) Neighborhood Health Committees spearheaded community-driven strategies via community action planning and ultimately strengthened the link between communities and health facilities. Conclusion: Broader health systems strengthening and strong partnerships between various levels of the government, communities, and external organizations were critical factors that accelerated vaccine coverage in Zambia. These partnerships were leveraged to strengthen the overall health system and healthcare governance.